2008
DOI: 10.1007/s00268-008-9631-8
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Resection for Metastatic Head and Neck Cancer

Abstract: The current practice of pulmonary metastasectomy for head and neck cancers in our institution was well justified. A disease-free interval equal to or longer than 12 months, nonsquamous cell carcinoma, and female sex might be relevant to a better prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 23 publications
5
49
1
4
Order By: Relevance
“…However, we found that the pattern of DM in the p16-positive patients, although slightly trending towards wider disease spread, as reported in previous studies, 17,20,21 was not significantly different than the p16-negative patients (p=0.615). We also noted that DM in p16-positive OPSCC, particularly pulmonary oligometastatic disease, was relatively indolent, treatment-responsive and was associated with longer survival.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, we found that the pattern of DM in the p16-positive patients, although slightly trending towards wider disease spread, as reported in previous studies, 17,20,21 was not significantly different than the p16-negative patients (p=0.615). We also noted that DM in p16-positive OPSCC, particularly pulmonary oligometastatic disease, was relatively indolent, treatment-responsive and was associated with longer survival.…”
Section: Discussionsupporting
confidence: 85%
“…Pattern of DM was characterized as oligometastasis (limited to 1–2 anatomic sites or ≤ 3 metastatic foci in one anatomic site), disseminating (> 2 anatomic sites), or explosive 20 (≥ 4 foci of metastasis at one anatomic site), akin to the definitions by Huang et al 5,10 Post-DM DSS was calculated from the time of DM detection to death from disease (i.e. distant metastasis or disease progression at the distant and/or the locoregional site).…”
Section: Methodsmentioning
confidence: 99%
“…Geara et al reported similar results in 103 metastatic NPC patients who treated with radiotherapy and chemotherapy (2 yeras-OS, 45%) for their metastases had a significantly better survival than those received no treatment (2 years-OS, 14%) or single chemotherapy (2 years-OS, 18%, P = 0.001) [22]. In addition, some long-term survivors aggressively treated with pulmonary metastasectomy in combination with chemotherapy were also reported in NPC patients with intrathoracic metastasis(es) alone [10,12,13,20,28-30]. Collectively, these data suggests an indication for combined therapy in selected metastatic NPC patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, in various studies the 5-year survival rate after pulmonary metastasectomy of SCCHN ranged between 26.5 and 59.5%, although some of these studies included non-SCCHN [49][50][51][52][53][54]. Shiono and colleagues reported the largest series of pulmonary resections for squamous cell metastases [50].…”
Section: Surgery For Lung Metastasesmentioning
confidence: 99%